O projeto nacionalista de João Goulart: análise dos discursos de 1961 a 1964 - Silva, Aline de Vasconcelos (2012)
Central objective of this research is an analysis of speeches of João Goulart, articulated between September 07, 1961 and March 31, 1964 (time when he was the President of the Republic), searching to extract its conceptual specificities, propositions and bounds, within of the historical process which he represented, indicating the existing organic bond between the propositions and appeals of such speech and the moment of intense political movements and debates on country directions of the Brazilian history. Starting by the entirety of the speech collection, we identify the main topics discussed, around which Goulart's most relevant propositions defended at the time of his government. Such themes are grouped among three axes: economic emancipation and basic reforms, with an emphasis on land reform; independent policy for international relations between Brazil and United States and Brazil and Latin America; and unstableness of legal order